The Role of Trade Unions in Addressing the psychological Health of Working Women Victimized by Sexual Harassment in Algeria: A Case Study of the National Independent Trade Union of Public Administration Employees – Constantine - BENAYACHE, Houria (Journal of Human Sciences, 2025)
Trade union organizations seek to try to support individuals experiencing difficulties in the work place, as currently trade union work is not based solely on negociating collective agreements but rather by moving towards comtemporary issues such as psychosocial risks that have a negative impact on worker’s psychological and physical health. Considering that sexual harassment is a type of risk that working women are exposed to and which has a direct impact on their psychological health and the development of their professional path , this study aims to reveal the types of supports provided by the national independent union of public administration employees in Constantine to preserve the psychological health of working women who are victims of sexual harassment.